STUDY ON REDUCTION OF METALS CONTENT Fe, Ni and Cu ON SEPARATING LIQUID WASTE SYSTEM WITH HIGH GRADIENT MAGNETIC SEPARATION (HGMS) USING ADSORBENT NANOPARTICLES - Dhafid Etana Putra (Indonesian Journal of Physics and Nuclear Applications, 2018)
Research has been carried out to determine the effective level of artificial metals waste purification such as Cu, Ni and Fe using High Gradient Magnetic Separation (HGMS). Electromagnetic filter is made from Polyvinyl Chloride (PVC) pipe with 1-inch in diameter and coiled by wire (0,45 mm in diameter), small pipes as a filter with diameter of 500 m consisting of 1173 coil. Purification is done by varying the magnetic field strength i.e 2,3 Gs, 5,1 Gs and 7,7 Gs. In this investigation, three treatments are given by changing the magnetic field direction, i.e the directions of the magnetic field are parallel, antiparallel and perpendicular in respect to the sample flow. And then, purification samples were analyzed using Atomic Absorption Spectroscopy (AAS). The result showed that the percentage of Cu tends to decrease, Ni constant and Fe increase. Magnetic field with opposite direction to the sample flow, percentage of Cu ( II ) i.e 92.90% , 94.96% , 93.15% and perpendicular to the sample flow i.e 96.58% , 94.71% , 95.67%. Magnetic field with opposite direction to the sample flow, the percentage of Ni ( II ) i.e 99.16% , 99.11% , 99.20% and perpendicular to the sample flow i.e 99.32% , 99.38% , 99.30%. The percentage of Fe (II) maximally in the magnetic field with opposite to the sample flow i.e 100%, 100%, 100% and perpendicular to the sample flow i.e 100%, 100%, 100%. This result is caused by the Fe (II), a ferromagnetic material, which has a spontaneous magnetic moment and a little valence electrons paired compared to Cu (II) and Ni (II). So, when the magnetic field is applied to the artificial waste water, spin orientation in Fe (II) will easily tend to align and attach to small pipes in the HGMS system